A Region of the N-terminal Domain of Meningococcal Factor H Binding Protein that Elicits Bactericidal Antibody across Antigenic Variant Groups - Beernink, Peter T. (2009)
Meningococcal factor H-binding protein (fHbp) is a promising vaccine antigen. Previous studies described three fHbp antigenic variant groups and identified amino acid residues between 100 and 255 as important targets of variant-specific bactericidal antibodies. We investigated residues affecting expression of an epitope recognized by a murine IgG2a anti-fHbp mAb, designated JAR 4, which cross-reacted with fHbps in variant groups 1 or 2 (95% of strains), and elicited human complement-mediated, cooperative bactericidal activity with other non-bactericidal anti-fHbp mAbs with epitopes involving residues between 121 and 216. From filamentous bacteriophage libraries containing random peptides that were recognized by JAR 4, we identified a consensus tripeptide, DHK, that matched residues 25-27 in the N-terminal domain of fHbp. Since DHK was present in both JAR 4-reactive and non-reactive fHbps, the tripeptide was necessary but not sufficient for reactivity. Based on site-directed mutagenesis studies, the JAR 4 epitope could either be knocked out of a reactive variant 1 fHbp, or introduced into a non-reactive variant 3 protein. Collectively, the data indicated that the JAR 4 epitope was discontinuous and involved DHK residues beginning at position 25; YGN residues beginning at position 57; and a KDN tripeptide that was present in variant 3 proteins beginning at position 67 that negatively affected expression of the epitope. Thus, the region of fHbp encompassing residues 25 to 59 in the N-terminal domain is important for eliciting antibodies that can cooperate with other anti-fHbp antibodies for cross-reactive bactericidal activity against strains expressing fHbp from different antigenic variant groups.